Developing a compact load cell to measure thrust and torque in small propeller testing - da Silva, Gabriel Pereira Gouveia [UNESP]; Eguea, João Paulo; Ciaramicoli, Lucas Miasiro; Cerón-Muñoz, Hernán Darío; Catalano, Fernando Martini (Springer Nature, 2025)
The development of electric aircraft propulsion systems has brought the need for further advancements in the design and testing of small-scale propellers, particularly for emerging applications such as distributed electric propulsion aircraft, electric vertical takeoff and landing vehicles, and drones. This need also extends to the development of horizontal axis wind turbines, autonomous underwater vehicles, tidal turbines, and reduced-scale testing of marine propellers. This study introduces a new load cell design capable of simultaneously measuring thrust and torque in small propeller systems. Unlike commercially available solutions, the proposed design integrates separate deformable elements for each measurement while ensuring compactness and low manufacturing cost. The iterative development process included proof of concept through finite element analysis, experimental calibration, and evaluation of cross-talk effects, leading to an optimized second-generation prototype with improved durability and measurement accuracy. The final design of the load cell demonstrates robust performance in thrust and torque measurements while addressing the limitations of the initial prototypes. These improvements provide a reliable solution for experimental propeller research. The main scientific contribution of this work lies in providing an open source, customizable, and cost-effective load cell capable of decoupled thrust and torque measurements with performance comparable to commercial systems.